Kearifan Lokal dan Kesetaraan Gender dalam Keluarga Etnis Dayak - Sara, Sabina; Widiarti, Febi; Musa, Dahniar Th.; Junida, Dwi Surti (Pusat Studi Wanita dan Keluarga UGM, 2024)
The study aims to explore the local wisdom of the Dayak community in relation to the concept of gender equality in everyday life within the family of Dayak communities. This research uses a qualitative method approach. Aim to dig and understand the meanings associated with local wisdom and gender equality in the family. From the qualitative methods the researchers collected data through observations carried out directly in the Pontianak town of Ambawang. The data collection is also an in-depth interview with several Dayak ethnic families. The process of data analysis is done by recording field notes, then collecting, classifying the data to interrelate. The results of this study show that the cultural values and traditional knowledge of the Dayak ethnic community towards women in Dayak societies are of paramount importance, by showing that gender equality and recognition of the role of women can contribute to the sustainable development and well-being of societies. The results of this study provide an overview of gender equality practices based on local wisdom of the Dayak community, which differs from the concept of genders equality in general. The implications of this discovery can give a deeper understanding of the local culture and wisdom of a society can shape patterns of relationships and gender distribution in the family.